Sociology 571 - Sociology of the Life Course: Midterm Examination - Carr, Deborah (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Instructions: You must provide answers to three of the following four questions. Be sure to answer each part of the questions you’ve selected. Your answers must incorporate information provided in required readings and in lecture. You may also feel free to draw on recommended readings as well as articles you have read for other classes and as part of your own research. You should limit each answer to roughly 5 pages of double-spaced type.(Exam to be used with Sociology 571 - Sociology of the Life Course syllabus)